MODELING OF TIDAL PROPAGATION PROCESSES IN THE MEKONG RIVER ESTUARY DURING DRY SEASON - Duong, Pham Xuan (Vietnam Journal of Marine Science and Technology, 2006)
MODELING OF TIDAL PROPAGATION PROCESSES IN THE MEKONG RIVER ESTUARY DURING DRY SEASON